Factors associated to the quality of the IPUEC from the prism of the institutional evaluation - Marrero Salazar, Francisca Ramona; Torres Fernández, Paúl Antonio (Avances en Supervisión Educativa, 2015)
Cuba is turning into significant transformations amidst a prolonged and deep economic crisis. Nevertheless, the achievements reached regarding education cannot he questioned. In this context, institutional evaluation in senior high school institutes in the countryside (IPUEC), is presented as an important pivot for the design of policies that contribute to make the right to education sustainable. This article as part of the author doctoral thesis, exposed an experience in the determination of the factors associated to students formation, that as its basic from the systematizing of the theory of educational evaluation, as well as an ex post fact study for the determination the what a one to advisement as content of the institutional evaluation. These results have stimulated adjustments within educational policies regarding the current relevancy of senior high school in the countryside.